Price satisfaction and producer loyalty: The role of mediators in business to business relationships in Kenyan mango supply chain - Mutonyi, Sarah; Beukel, Karin; Gyau, Amos; Hjortsø, Carsten Nico (Emerald Publishing Limited, 2016)
The purpose of this paper is to investigate which dimensions of price satisfaction influence producers’ trust in buyers and assess the mediating role of such trust in the relationship between price satisfaction and producer loyalty in fresh fruit supply chains.A cross-sectional study design using both semi-structured interviews and structured questionnaires was used. The study was conducted in the eastern part of Kenya and included 600 smallholders. Data was analysed using structural equation modelling.The results show that price fairness, price reliability, and relative price are dimensions of price satisfaction that affect producers’ trust in the buyer. Moreover, trust between the producer and the buyer is found to be a strong mediator between price satisfaction and producer loyalty. The findings support recent studies about trust and its mediating role.The paper is based on a cross-sectional study design, limiting the causal inferences which can be drawn. Producers’ preferences change with time and future studies should be based on longitudinal designs.This paper shows the relationship between the multidimensional nature of price satisfaction and producer loyalty with trust as a mediating variable in the business-to-business (B2B) context. Although B2B relationships have been shown to be of great importance for smallholders in enhancing business performance with their buyers, little attention has been given to the role of trust as a mediator. This study offers interesting insights into the how trust plays a mediating role between price satisfaction and loyalty in a developing country context.